A Systematic Review on the Bacterial Infestation of Aquaculture Farms in Selected Regions of the Philippines and its Impact on the Fisheries Industry and Public Health - Cid, Aleczandra Marie T.; Sarapuddin, Shaira B.; Jr., Rolando M. Santos; Fernandez, Jeizelle S.; Divinagracia, Angel Marie L.; Garcia, Christian Jocel S.; Untalan, Alyssa Claire L.; Albelda, Princess B.; Cano, Earl Adriane A. (Asian Journal of Biological and Life Sciences)
Background:Regions III and IV-A of the Philippines, with their vast natural water bodies and myriad marine resources, have been among the country’s leading fish producers. However, having situated near the infamously known “dirty” Manila Bay, aquaculture farms in these provinces are vulnerable to various potential contaminants.Methods:A systematic search was conducted to gather current reports and studies from JSTOR, Google Scholar, PubMed, ResearchGate, ScienceDirect, and other outside sources regarding possible bacterial infestations in aquaculture farms within these regions, including their implications on their respective fisheries sector. After removing duplicates and screening for eligibility, 40 studies were considered amongst 415 publications from five databases and 58 records from external sources.Results:The results of this systematic review demonstrated that aquaculture farms in Central Luzon and Calabarzon have a significant economic impact on the Philippine fisheries industry and a diversity of resources is evident despite natural disasters. The results also revealed that bacterial infestations seem to be observable in some provinces in the regions, which can be linked to managerial and environmental concerns in these areas, despite having very few reports denoting the existence of the issue in aquaculture facilities of both regions.Conclusion:Prompt investigations into the aquaculture farms’ water conditions and contamination must be conducted to provide appropriate and cost-effective solutions to respond to this public health emergency. Other specific biosecurity concerns that were also presented can be further clarified to aid in the provision of resolutions.
Keywords: Aquaculture Farming; Bacterial Infestation; Fisheries; Philippines; Public health